2018
DOI: 10.1038/s41598-018-29151-w
|View full text |Cite
|
Sign up to set email alerts
|

The membrane-associated fraction of cyclase associate protein 1 translocates to the cytosol upon platelet stimulation

Abstract: Platelets undergo profound shape changes upon adhesion to damaged blood vessel walls that are mediated by reorganisation of the actin cytoskeleton in response to receptor-mediated signalling cascades. The highly conserved 56 kDa multidomain cyclase associated protein 1 (CAP1) works in concert with cofilin and profilin to modulate actin filament turnover by facilitating cofilin-mediated actin filament severing and depolymerisation and catalysing profilin-mediated regeneration of actin monomers for reutilisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
(62 reference statements)
1
8
0
Order By: Relevance
“…3 a). Integrin αIIb and GAPDH were used as a marker of the membrane and cytosolic fractions of platelet lysates, respectively [ 36 , 37 ]. Ser24-phosphorylated Dab2 was increased in thrombin- and PAR1 peptide-stimulated platelets and was mainly found in the membrane fraction, while Ser723-phosphorylated Dab2 was mainly found in the cytosolic fraction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 a). Integrin αIIb and GAPDH were used as a marker of the membrane and cytosolic fractions of platelet lysates, respectively [ 36 , 37 ]. Ser24-phosphorylated Dab2 was increased in thrombin- and PAR1 peptide-stimulated platelets and was mainly found in the membrane fraction, while Ser723-phosphorylated Dab2 was mainly found in the cytosolic fraction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Saponins work by stimulating the formation of new cells, or called Growth Factor. Causing the multiplication and growth of blood vessel endothelial cells, vascular smooth muscle cells and fibroblasts, causing cellular growth which ultimately repair damaged blood vessel walls [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…They are usually visible during early adhesion and spreading [ 51 ]. We have recently shown that CAP1, a protein involved in recycling of actin monomers, is also a component of the actin nodule ring [ 4 ], therefore we speculate that coronins too might contribute to the actin filament turnover of these highly dynamic structures.…”
Section: Discussionmentioning
confidence: 99%
“…Remodeling of the cytoskeleton, formed by a network of actin filaments and a marginal ring of microtubules and associated proteins constitutes a crucial aspect of platelet function and is the result of multiple exquisitely integrated signaling cascades [2]. A plethora of proteins with various biochemical activities is responsible for the dynamics of actin remodeling during platelet activation, including actin nucleators like formins and the Arp2/3 complex and their regulators (WAVE, WASP), monomeric actin-binding proteins like profilin, β-thymosin and the cyclase-associated protein (CAP) and others like gelsolin, cofilin, and coronins [3][4][5].…”
Section: Introductionmentioning
confidence: 99%